2007
DOI: 10.1152/ajprenal.00511.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic blood pressure load and nephropathy in the ZSF1 (fa/facp) model of type 2 diabetes

Abstract: Diabetes and increased blood pressure (BP) are believed to interact synergistically in the pathogenesis and progression of diabetic nephropathy. The present studies were performed to examine if there were differences in BP load and/or protective renal autoregulatory capacity between the obese diabetic Zucker fatty /spontaneously hypertensive heart failure F1 hybrid (ZSF1) (fa/fa cp) rats and their lean controls. By approximately 26 wk of age, ZSF1 (n = 13) but not their lean controls (n = 16) had developed sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 70 publications
(162 reference statements)
4
47
2
Order By: Relevance
“…Consistent with the above hypothesis, the present data indicate that renal autoregulation was markedly impaired in ZDF rats at spontaneous levels of mean BP, reducing preglomerular vascular tone and participating in glomerular hyperfiltration. However, our results seem different from those of Griffin et al [35], who found that renal autoregulation was preserved in Zucker spontaneously hypertensive rats, an offspring from the breeding of Zucker obese and spontaneously hypertensive rats. Genetic differences between ZL and ZDF rats, such as differences in leptin receptors, might cause the autoregulatory curve to shift toward higher pressure in ZDF rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the above hypothesis, the present data indicate that renal autoregulation was markedly impaired in ZDF rats at spontaneous levels of mean BP, reducing preglomerular vascular tone and participating in glomerular hyperfiltration. However, our results seem different from those of Griffin et al [35], who found that renal autoregulation was preserved in Zucker spontaneously hypertensive rats, an offspring from the breeding of Zucker obese and spontaneously hypertensive rats. Genetic differences between ZL and ZDF rats, such as differences in leptin receptors, might cause the autoregulatory curve to shift toward higher pressure in ZDF rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Data were acquired at 1,000 Hz in 10 s bursts every 2 min. Systolic BP is reported in order to maintain consistency with previous studies in the literature [7,14,16] and because it is more closely correlated with organ damage than mean or diastolic BP [10]. Body weight and blood glucose were measured twice weekly in all animals; blood samples were acquired from the tail of conscious, unrestrained rats.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension is generally accepted to be a major contributor to the development of nephropathy in diabetes [2,3] and accelerates all other forms of nephropathy [4]. There is also considerable evidence for the importance of genetic and functional factors in determining target organ susceptibility [5][6][7]. In uncomplicated type 1 or type 2 diabetes, there is a high incidence of diabetic hyperfiltration, which results from glomerular hypertension, presumably because of inappropriately low pre-glomerular resistance [2,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both lean and obese animals inherit the gene for hypertension from the SHR strain and have similarly elevated blood pressure, but only obese ZSF1 rats (fa/fa cp ) develop dyslipidemia, hyperglycemia, and renal sclerosis and fibrosis (Tofovic et al 2000, Zhang et al 2007, Rafikova et al 2008. Recently, Griffin et al (2007) demonstrated that the development of kidney disease in the ZSF1 rat model is largely independent of hypertension and/or its potential renal transmission. Thus, the ZSF1 rat model allows for separation of renal pathophysiology strictly due to obesity, hyperglycemia, and dyslipidemia from changes due to hypertension.…”
Section: Introductionmentioning
confidence: 99%